CONTRIBUTION OF EDUCATION TO ECONOMIC DEVELOPMENT: LESSONS FROM JAPAN - , Robertus Heru Susanto, S.E. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Many developing countries already realized the important of education to economic development. It is believed that the education sector is a crucial factor in supporting sustainable economic development and boosting economic growth. However, Indonesia as a developing country should learn how to build education for the advancement of her economic development. This is an essential issue due to Indonesia still left behind from other neighborâs countries. This paper wants to explore the contribution of education to economic development and tries to make a clear connection between education and economic development. Next focal paper is wants to reveal the role of Japanese education to her economic development. By learning from the success of Japan, this might be used for the lessons of Indonesian education, and may contribute in how to determine and direction the future of education policy should be set for Indonesia. In Indonesia cases, the analysis is applied to determinant the achievement of national education development during New Order era. Overview of development of education will conduct in historical manner for both countries. In this paper find that in the era of Tokugawa basic education already spread among class society without government intervenes and Confucian value become national virtue. Since the purpose of Meiji era was to build a strong army through economic power, it is necessary to reform the education system in order to absorb the Western technologies. Meiji government took heavy intention to universal education as part of economic catch-up. Vocational education became a second pace in part of economic catch-up. After fifteen years from the Pacific war, in 1960 government announced income double plan policy. In order to realize the plan, the Economic Planning Agency studied and identified the specific requirement for labor power to support this plan. In addition, some observations to Japanese schools also conducted in order to give a better perspective about education in Japan. Meanwhile, from the analysis, Indonesia had reach universal basic education stage in Pelita IV, but this achievement did not follow with proper development of secondary education. The lack of financial resources becomes a major obstacle in developing national education, besides technical and policy issues. To supporting long-term sustainable economy, development of national education is become a necessary prerequisite, not only in quantity but also in the quality development should be considered by the policymaker. In this paper propose several recommendations regarding the development of national education.